Enhancing soybean germination and vigor under water stress: the efficacy of bio-priming with sodium carboxymethyl cellulose and gum arabic - Almakas, Aisha; Elrys, Ahmed S.; Desoky, El-Sayed M.; Al-Shuraym, Laila A.; Alhag, Sadeq K.; Alshaharni, Mohammed O.; Alnadari, Fawze; NanNan, Zhang; Farooq, Zunaira; El-Tarabily, Khaled A.; Zhao, Tuanjie (Frontiers in Plant Science, 2025)
Seed priming can significantly enhance the tolerance of soybean against different environmental stresses by improving seed water uptake and modulating stress-response mechanisms. In particular, seed priming with sodium carboxymethylcellulose (SCMC) and gum Arabic (GA) can support seeds to withstand extreme conditions better, promoting more consistent germination and robust seedling establishment, which is crucial for achieving stable agricultural yields. The present study investigated the effects of seed priming using a combination of SCMC and GA (10% CG) on the germination, growth, and biochemical responses of six soybean varieties under drought and flooding stress conditions. The results revealed significant differences among varieties and applied treatments on germination, vigor, and physiological traits. Under drought stress, seed priming with 10% CG significantly improved germination percentage, germination rate, shoot length, root length, and biomass compared to unprimed seeds. Notable reductions in malondialdehyde (MDA) content and enhanced antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), suggest that 10% CG priming mitigates oxidative damage through enhanced antioxidant defense mechanisms. Moreover, 10% CG seed priming improved germination and growth parameters under flooding stress, but the advantages were less significant. In addition, the priming treatment significantly reduced electrolyte conductivity (EC) across all varieties compared to unprimed seeds, indicating improved membrane stability. Overall, 10% CG seed priming was more effective under drought and flooding conditions, demonstrating a potential strategy for enhancing stress tolerance in soybean varieties.